FIBRILLATION OF VENTRICLES AND VENTRICLESЫE TACHYCARDIA BASIC PROVISIONS AND DIAGNOSTIC CRITERIA - G.T. Mamedova (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Keywords: Fibrillation, flicker, Uncoordinated cutting of ventricular tremblesdefibrillation dilatatic cardiomyopathy, angiography,cardioversion